2013
DOI: 10.1016/j.jconrel.2012.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of drug delivery from autocatalytically degradable PLGA microspheres — A review

Abstract: PLGA microspheres are widely studied for controlled release drug delivery applications, and many models have been proposed to describe PLGA degradation and erosion and drug release from the bulk polymer. Autocatalysis is known to have a complex role in the dynamics of PLGA erosion and drug transport and can lead to size-dependent heterogeneities in otherwise uniformly bulk-eroding polymer microspheres. The aim of this review is to highlight mechanistic, mathematical models for drug release from PLGA microspher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
175
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(178 citation statements)
references
References 84 publications
(105 reference statements)
2
175
0
1
Order By: Relevance
“…The rest release superimposed the polymer erosion and often became extremely slow. 25,26 The in vitro release of BSA showed that the polymer concentration played an important role in controlling the release from the microspheres. A higher polymer concentration resulted in a microsphere layer with higher density and thickness.…”
Section: Bsa Release From Microspheres and Microsphere Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…The rest release superimposed the polymer erosion and often became extremely slow. 25,26 The in vitro release of BSA showed that the polymer concentration played an important role in controlling the release from the microspheres. A higher polymer concentration resulted in a microsphere layer with higher density and thickness.…”
Section: Bsa Release From Microspheres and Microsphere Degradationmentioning
confidence: 99%
“…27 PLGA micro sphere degradation caused a dramatic pH drop in the release medium after incubation. 26,28 Unlike PLGA, a relatively neutral pH was retained in the PBS for BSA-loaded microspheres formulations, thus providing a suitable environment for proteins. Clearly, almost no acidic degradation products were released from the BSA-loaded microspheres, and thus no acidic micromilieu would be produced.…”
Section: Degradation Of Microspheres and Ph Change Of Pbsmentioning
confidence: 99%
“…Towards this, computational modelling offers an efficient framework to understand the behaviour of biodegradable implants. Many models have been proposed to describe the degradation of biodegradable polymers (Sackett and Narasimhan, 2011) including PLGA (Ford Versypt et al, 2013). Reaction-diffusion models have been applied to a range of aliphatic polyesters.…”
Section: Introductionmentioning
confidence: 99%
“…Reaction-diffusion models have been applied to a range of aliphatic polyesters. Among these models, the ones which account for the autocatalytic effect are the most comprehensive, as autocatalysis plays a strong role in the degradation mechanism (Chen et al, 2011;Ford Versypt et al, 2013;Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, most (if not all) of the examples of autocatalysis by this mechanism take place in heterogeneous environments where other factors play an important role in the observed kinetics. 10,11 In the hydrolytic degradation of polyesters such as poly(lactic acid), the rate acceleration in loss of mass has been attributed to the increasing concentration of terminal carboxylic acid groups. 12 However, rate acceleration with liquid esters was demonstrated to arise by a physical mechanism whereby the product effectively aids in the solubilisation of the reactant.…”
Section: Page 2 Of 10mentioning
confidence: 99%